The Role of Civil Society in Screening Asylum in Brazil - De Castro, Flavia Rodrigues (2020)
The refugee status determination (RSD) process in Brazil is governed by the National Committee for Refugees (CONARE) - the administrative body responsible for assessing the credibility of asylum seekers and deciding all asylum cases in the country – with the active participation of civil society. This paper aims to analyze the role of civil society in this process through the epistemic practices responsible for judging who can be categorized as a refugee. In order to do this, a theoretical approach that emphasizes the production of epistemic injustices in credibility analysis will be used here.